2018
DOI: 10.3389/fmars.2018.00361
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Bacterioplankton to Environmental Disturbance: A Review of Baltic Sea Field Studies and Experiments

Abstract: Bacterioplankton communities regulate energy and matter fluxes fundamental to all aquatic life. The Baltic Sea offers an outstanding ecosystem for interpreting causes and consequences of bacterioplankton community composition shifts resulting from environmental disturbance. Yet, a systematic synthesis of the composition of Baltic Sea bacterioplankton and their responses to natural or human-induced environmental perturbations is lacking. We review current research on Baltic Sea bacterioplankton dynamics in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 141 publications
(156 reference statements)
1
31
0
Order By: Relevance
“…Structural changes to bacterial communities and metabolism could consequently have profound effects on the fate and cycling of carbon within planktonic food webs. Our results link microbial community structure and function in the Baltic Sea to ongoing shifts in the phytoplankton community structure (Lindh and Pinhassi 2018). The data suggest that specific diatoms release high-quality DOM that enhances the growth of copiotrophic bacteria with high production rates, in turn favoring the recycling of carbon through the microbial loop.…”
Section: Links Between Bacterial Community Composition and Ecosystem Functioningmentioning
confidence: 70%
“…Structural changes to bacterial communities and metabolism could consequently have profound effects on the fate and cycling of carbon within planktonic food webs. Our results link microbial community structure and function in the Baltic Sea to ongoing shifts in the phytoplankton community structure (Lindh and Pinhassi 2018). The data suggest that specific diatoms release high-quality DOM that enhances the growth of copiotrophic bacteria with high production rates, in turn favoring the recycling of carbon through the microbial loop.…”
Section: Links Between Bacterial Community Composition and Ecosystem Functioningmentioning
confidence: 70%
“…Similar bacterial responses were observed in a mesocosm study, where the growth of diatoms resulted in higher bacterial production and higher dominance of Flavobacteriia, Gammaproteobacteria and Cytophagia than in the presence of dinoflagellates 23 . The robustness of the observed patterns in our study, linking BCC and functioning, are essential in microbial ecology since the studies that explore these relationship are scarce in the Baltic Sea 63 .…”
Section: Discussionmentioning
confidence: 69%
“…The effect of disturbances on the composition and function of communities can be addressed in terms of resistance, recovery and resilience, where resistance is defined as the insensitivity to a disturbance and recovery and resilience (more specifically engineering resilience) as the degree and rate of recovery after a disturbance 5 . Previous reviews of the literature have shown that microbial communities are mostly not resistant, instead they often change in composition and function in response to disturbances 5 8 . In contrast, recovery and resilience are still rarely studied, so it remains unclear under which circumstances and at which rates compositional recovery occurs in microbial communities 5 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous reviews of the literature have shown that microbial communities are mostly not resistant, instead they often change in composition and function in response to disturbances 5 8 . In contrast, recovery and resilience are still rarely studied, so it remains unclear under which circumstances and at which rates compositional recovery occurs in microbial communities 5 , 8 . Changes in community composition following a disturbance may also underlie changes in ecological function, although this relationship is not well understood 9 .…”
Section: Introductionmentioning
confidence: 99%